Copper-enriched hydroxyapatite coatings obtained by high-velocity suspension flame spraying. Effect of various gas parameters on biocompatibility - Long-Quan R. V. Le; M. Carolina Lanzino; Matthias Blum; Anika Höppel; Ali Al-Ahmad; Andreas Killinger; Rainer Gadow; Wolfgang Rheinheimer; Michael Seidenstuecker (Journal of Materials Science: Materials in Medicine)
Abstract Hydroxyapatite (HAp)-coated bone implants are frequently used for orthopaedic or dental implants since they offer high biocompatibility and osteoconductivity. Yet, problems such as infections, e.g. periprosthetic joint infections, occur when implanting foreign material into the body. In this study, HAp coatings were produced via high-velocity suspension flame spraying (HVSFS). This method allows for the production of thin coatings. We investigated the effects of different gas parameters on the coating properties and on the biocompatibility, which was tested on the human osteosarcoma cell line MG63. Furthermore, Copper (Cu) was added to achieve antibacterial properties which were evaluated against standard microorganisms using the airborne assay. Three gas parameter groups (low, medium, and high) with different Cu additions (0 wt.%, 1 wt.% and 1.5 wt.%) were evaluated. Our findings show that porosity as well as hardness can be controlled through gas parameters. Furthermore, we showed that it is possible to add Cu through external injection. The Cu content in the coating as well as the release varies with different gas parameters. Both antibacterial efficacy as well as biocompatibility are affected by the Cu content. We could significantly reduce the amount of colony-forming units (CFU) in all coatings for E. coli, CFU for S. aureus was reduced by adding 1.5 wt.% of Cu to the coating. The biocompatibility testing showed a cytotoxicity threshold at a Cu-release of 14.3 mg/L in 120 hours. Based on our findings, we suggest medium gas parameters for HVSFS and the addition of 1 wt.% Cu to the coating. With these parameters, a reasonable antibacterial effect can be achieved while maintaining sufficient biocompatibility. Graphical Abstract